Polymorphonuclear Leukocyte Inhibition of Monocytes/Macrophages in the Foreign Body Reaction - Kirk, James T. (2010)
The effect of polymorphonuclear leukocytes (PMNs) on the subsequent chronic phase macrophage-mediated foreign body reaction has not been previously investigated. Furthermore, while monocyte/macrophage-produced cytokines such as GM-CSF, G-CSF, or IL-1β have been shown to increase PMN survival in vitro, few studies have examined the impact of directly co-cultured monocytes/macrophages on PMN viability. To this end, we used our established in vitro system of interleukin (IL)-4-induced monocyte-derived macrophage fusion to examine the role of PMNs in the subsequent foreign body reaction. Monocytes were directly cultured with PMNs for 3 days prior to the addition of IL-4 to induce monocyte-derived macrophage fusion to facilitate foreign body giant cell (FBGC) formation by Day 7 and Day 10 of culture. Optical microscopy was used to quantitatively determine adherent monocyte density, percent macrophage fusion, and FBGC density. A colorimetric MTT assay was used to assess PMN viability for direct co-cultures of monocytes/macrophages and PMNs. Our results strongly suggest that the presence of PMNs inhibit IL-4-induced macrophage fusion and FBGC formation. Additionally, our findings demonstrate that co-cultures containing PMNs and monocytes/macrophages increases PMN survival with respect to PMN-only cultures in vitro.